DIFFERENCES IN PUBLIC ACCOUNTANT CAREER PERCEPTIONS: A CROSS-INSTITUTIONAL STUDY OF STUDENTS AT MUHAMMADIYAH UNIVERSITY OF BANDUNG AND UNIVERSITI KUALA LUMPUR - Oktaviani, Leni; Zulkarnian, Aira Farhana binti; Pratiwi, Inugrah Ratia; Suarsa, Abin; Kasbun, Nur Fatin (Jurnal Akuntansi Bisnis, 2026)
Background: The accounting profession is evolving rapidly due to globalization and technological development, significantly influencing students' perception of public accountant careers. Objective: This study aims to compare the perceptions of accounting students in Indonesia and Malaysia toward public accountant careers, focusing on five key variables: career stability, workload, globalization, technology, and academic support. Research Methods: This research employed a quantitative descriptive-comparative approach, involving 66 students from Universitas Muhammadiyah Bandung (Indonesia) and Universiti Kuala Lumpur (Malaysia), selected using stratified random sampling. Data were collected through Likert-scale questionnaires and analyzed using descriptive statistics and independent samples t-tests. Research Results: The results revealed significant differences in perceptions regarding career stability, workload, and technology, with UniKL students showing more favorable views. However, no significant differences were found in globalization and academic support. Originality of Research: This research contributes new insights through a cross-country comparison of accounting students’ career perceptions, offering practical implications for educational institutions to align curricula with regional and global industry expectations.